The Border–Non-Border Areas Disparities in Hospital Utilization in Kalimantan Island, Indonesia (Medico Legal Update, 2021)
The border area is one area that needs government attention. The study was aimed at analyzing disparitiesin hospital use in Kalimantan based on the border-non-border area category. The study was conducted usingdata from the 2013 Indonesian Basic Health Survey. With the multi-stage cluster random sampling method,69,043 respondents were obtained. In the final stage, a Multinomial Logistic Regression test was performedto determine any disparities. The study results found that the utilization of inpatient at the hospital for thoseliving in the border area has a probability of utilization of 0.653 times compared to those who live in nonborder areas. Those who live in the border have a lower chance than those who live in non-border areasof using inpatient hospital. The results of the study also found 8 other predictors that influence hospitalutilization among adults in Kalimantan Island, Indonesia. The eight predictors are the type of place ofresidence, marital, education, work type, socioeconomic, health insurance, travel time, and transportationcost. It could be concluded that there was a disparity in hospital utilization in the border–non-border areasin Kalimantan Island, Indonesia. Those living in border areas have a lower likelihood of inpatient utilizationthan those living in non-border areas.